2016
DOI: 10.1113/ep085783
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia in obese Zucker rats: cardiometabolic and inflammatory effects

Abstract: What is the central question of this study? This study addresses the relative impact of obesity and intermittent hypoxia in the pathophysiological process of obstructive sleep apnoea by investigating the metabolic, inflammatory and cardiovascular consequences of intermittent hypoxia in lean and obese Zucker rats. What is the main finding and its importance? We found that obesity and intermittent hypoxia have mainly distinct consequences on the investigated inflammatory and cardiometabolic parameters in Zucker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…In addition to the type of hypoxemia, the duration of exposure is another parameter that could influence Ad circulating levels. Indeed, previous studies did not find any modification of Ad levels in rats submitted to intermittent or continuous hypoxia for 14 days, as well as in mice exposed to hypoxia for 21 days (Chaiban et al, 2008; van den Borst et al, 2013; Briançon-Marjollet et al, 2016). By contrast, after 8 weeks of exposure to continuous hypoxia (FiO 2 : 10%, 24 h/day), Chaiban et al (2008) observed an increased Ad level in hypoxemic mice.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to the type of hypoxemia, the duration of exposure is another parameter that could influence Ad circulating levels. Indeed, previous studies did not find any modification of Ad levels in rats submitted to intermittent or continuous hypoxia for 14 days, as well as in mice exposed to hypoxia for 21 days (Chaiban et al, 2008; van den Borst et al, 2013; Briançon-Marjollet et al, 2016). By contrast, after 8 weeks of exposure to continuous hypoxia (FiO 2 : 10%, 24 h/day), Chaiban et al (2008) observed an increased Ad level in hypoxemic mice.…”
Section: Discussionmentioning
confidence: 80%
“…This phenomenon can be attributed to an increased accumulation and intake of lipids due to inflammation in various organs and tissues, including the liver; alternatively, it might also be due to reduced activity and energy consumption. Obesity complicated by OSA has a high prevalence [ 23 ], although studies on the mechanism of obesity and OSA are relatively rare. St-Onge and Shechter suggested that frequent short sleep duration was the main manifestation in OSA patients due to frequent intermittent hypoxia that reduced sleep quality, leading to energy imbalance in the body and weight gain [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In lean mice, all types of hypoxia induced insulin resistance and increased circulating leptin levels, but only frequent IH (60 times/h) increased lipid peroxidation and TNF- α production by adipose tissue [ 72 ]. However, two weeks' exposure to IH did not increase serum leptin levels in both lean and obese Zucker rats [ 73 ], whereas leptin was upregulated by 2–5 weeks of IH in nonobese or diet-induced obese rats [ 74 , 75 ]. Such discrepancy in the results indicates that that hyperleptinemia in OSA might be modulated by severity and duration of IH and its interactions with an obese phenotype.…”
Section: Osa and Hyperleptinemiamentioning
confidence: 99%